Cognitive approaches to the assessment of sexual interest in sexual offenders - Thornton, D. (David); Laws, D. Richard; Wiley InterScience (Online service) (Chichester, UK ; Malden, MA : Wiley-Blackwell, 2009)
New for the Wiley Series in Forensic Clinical Psychology, Cognitive Approaches to the Treatment of Sexual Offenders describes and evaluates the current methods of measuring sexual interest in sex offenders - namely penile plethysmography, the Abel Assessment for Sexual Interest, Affinity 2.1, the Implicit Association Test, the Stroop test and the polygraph. The book also discusses how established cognitive assessment methods such as the attentional blink and the startle probe reflex can be adapted for use with sex offenders. It therefore brings together in one volume all the latest research an.
Penile plethysmography : strengths, limitations, innovations / D. Richard Laws -- The Abel assessment for sexual interests-2: a critical review / Susan J. Sachsenmaier & Carmen L.Z. Gress -- Affinity : the development of a self report assessment of paedophile sexual interest incorporating a viewing time validity measure / David V. Glasgow -- Cognitive modeling of sexual arousal and interest : choice reaction time measures / Carmen L.Z. Gress & D. Richard Laws -- The implicit association test as a measure of sexual interest / Nicola S. Gray and Robert J. Snowden -- Measuring child molesters' implicit cognitions about self and children / Kevin L. Nunes -- The rapid serial visual presentation test of sexual interest in child molesters / Vanja E. Flak, Anthony R. Beech & Glyn W. Humphreys -- Assessing sexual interest with the emotional Stroop test / Paul Smith -- Comparing two implicit cognitive measures of sexual interest : a pictorial modified Stroop task and the implicit association test / Caoilte Ciardha & Michael Gormley -- The startle-probe reflex : an alternative approach to the measurement of sexual interest / Jeffrey E. Hecker, Matthew W. King, and R. Jamie Scoular -- Postscript : steps towards effective assessment of sexual interest / David Thornton and D. Richard Laws.
Includes bibliographical references and index.
Print version record.
Keywords: Sex offenders -- Research; Child molesters -- Research; Paraphilic Disorders -- diagnosis; Sex Offenses -- psychology; Psychological tests; PSYCHOLOGY -- Mental Illness; Electronic books